2021
DOI: 10.3389/fimmu.2021.791319
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Mobilizes Insect Blood Cells to Infection Foci

Abstract: Innate immune responses are effective for insect survival to defend against entomopathogens including a fungal pathogen, Metarhizium rileyi, that infects a lepidopteran Spodoptera exigua. In particular, the fungal virulence was attenuated by cellular immune responses, in which the conidia were phagocytosed by hemocytes (insect blood cells) and hyphal growth was inhibited by hemocyte encapsulation. However, the chemokine signal to drive hemocytes to the infection foci was little understood. The hemocyte behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Instead of COX, specific peroxidases behave like COX in insects (Park et al, 2014). PGH 2 is then isomerized into different PGs using PGES (Ahmed et al, 2018), PGDS (Sajjadian et al, 2020), PGIS (Ahmed et al, 2021), and TXAS (Roy et al, 2021) in S. exigua . This PG biosynthetic pathway was also found in A. sapporensis by identification of the ortholog genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of COX, specific peroxidases behave like COX in insects (Park et al, 2014). PGH 2 is then isomerized into different PGs using PGES (Ahmed et al, 2018), PGDS (Sajjadian et al, 2020), PGIS (Ahmed et al, 2021), and TXAS (Roy et al, 2021) in S. exigua . This PG biosynthetic pathway was also found in A. sapporensis by identification of the ortholog genes.…”
Section: Discussionmentioning
confidence: 99%
“…Different PGs and their biosynthetic pathways have been identified in insects (Ahmed & Kim, 2021; Sajjadian et al, 2020); PGD 2 and PGE 2 induce immune responses, while PGI 2 suppresses these responses (Ahmed et al, 2021). A prostanoid such as thromboxane A 2 mediates hemocyte migration to the infection foci (Roy et al, 2021). All four EETs have been identified in a lepidopteran Spodoptera exigua and known to mediate cellular immune responses (Vatanparast et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we found that several thromboxanes, which are structurally similar to prostaglandins, were upregulated in mated queens over virgins ( Figure 7 & Figure S7 ). In the Lepidopteran Spodoptera exigua , thromboxanes are immunostimulatory 72,73 , and a thromboxane receptor has been characterized in Aedes and Anopheles mosquitoes 74 , but neither thromboxanes nor their receptors have been investigated in honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…A fungal pathogen, Beauveria bassiana (Bb), was isolated from a commercial product (LG Farm Hannong, Seoul, Korea). Metarhizium rileyi (Mr) was isolated from dead insects sourced from an onion field and M. guizhouense (Mg) was isolated from Rhinoceros beetle (Roy et al, 2021). The fungi were cultured in potato dextrose broth (Difco, Fisher Scientific Korea, Seoul, Korea) for 14 days with a shaking incubator at 180 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Among the numerous immune mediators that have been described to this point, eicosanoids play crucial roles in mediating immune responses against various pathogens (Kim et al, 2018a). Eicosanoids are a group of oxygenated C20 polyunsaturated fatty acids that includes prostaglandins, leukotrienes, and epoxyeicosatrienoic acids (Kim and Stanley, 2021). They are synthesized from a C20 precursor called arachidonic acid (AA), which is released from phospholipids by the catalytic activity of phospholipase A 2 (PLA 2 ) (Mouchlis and Dennis, 2019).…”
Section: Introductionmentioning
confidence: 99%